DETERMINATION OF TRACE NITRITE AS 4-(4-NITROBENZENAZO)- 1-AMINONAPHTHALENE COMPLEX BY EXTRACTION-SPECTROPHOTOMETRY - Choirul Amri; Dwi Siswanta; Mudasir Mudasir (Indonesian Journal of Chemistry, 2009)
A study of extraction-spectrophotometric method for the determination of trace nitrite as 4-(4-nitrobenzenazo)-1-aminonaphthalene complex using n-amylalcohol and chloroform as organic solvents has been done. Results of the study showed that extraction-spectrophotometric determination of nitrite using n-amylalcohol or chloroform was very sensitive and had low limit of detection. Extraction-spectrophotometric method of nitrite using n-amylalcohol gave range of linear concentration 0.000-0.054 mg/L NO2--N, detection limit of 2.09x10-4 mg/L NO2--N, and sensitivity of 34.514 ± 0.398 absorbance unit per mg/L of NO2--N. Meanwhile, extraction-spectrophotometric of nitrite using chloroform had range of linear concentration of 0.000-0.100 mg/L NO2--N, detection limit of 8.99x10-4 mg/L NO2--N, and sensitivity of 18.353 ± 0.456 absorbance unit per mg/L NO2--N.